10. Effect of Pressure and Drainage Duration to Protein Level in Dry Meat Acehnese (Sie balu) - Muarrif Tursina; Nurliana Nurliana; Muhammad Isa; Ismail Ismail; Herrialfian Herrialfian; Hamdan Hamdan (Jurnal Medika Veterinaria, 2018)
The aim of this research was to know effect of Pressure Duration to protein level in Dry Meat Acehnese (Sie balu). Thigh of fresh beef was used in this study (musculus semitendinosus) eight pieces, weighing 250 grams each. All of meats were in the pressed with a iron plate weight of 10 kg. The design of research used  a completely randomized design (CRD). All of meats were randomly divided into four treatments. First treatment (PO) as control, were not given pressure. Second treatment (P1) was given pressure during 6 hours. Third treatment (P2) was given pressure during the 12 hours and the four treatment (P3) was given pressure during 18 hours. Of results showed the pressure with 10 kg on meat significant effect on the protein content of  Aceh Sie balu (p 0.01). It was concluded that the pressure with weigher 10 kg increase the level protein sie balu during in process